Married Too Young? The Behavioral Ecology of ‘Child Marriage’ - Susan B. Schaffnit; David W. Lawson (Social Sciences, 2021)
For girls and women, marriage under 18 years is commonplace in many low-income nations today and was culturally widespread historically. Global health campaigns refer to marriage below this threshold as ‘child marriage’ and increasingly aim for its universal eradication, citing its apparent negative wellbeing consequences. Here, we outline and evaluate four alternative hypotheses for the persistence of early marriage, despite its associations with poor wellbeing, arising from the theoretical framework of human behavioral ecology. First, early marriage may be adaptive (e.g., it maximizes reproductive success), even if detrimental to wellbeing, when life expectancy is short. Second, parent–offspring conflict may explain early marriage, with parents profiting economically at the expense of their daughter’s best interests. Third, early marriage may be explained by intergenerational conflict, whereby girls marry young to emancipate themselves from continued labor within natal households. Finally, both daughters and parents from relatively disadvantaged backgrounds favor early marriage as a ‘best of a bad job strategy’ when it represents the best option given a lack of feasible alternatives. The explanatory power of each hypothesis is context-dependent, highlighting the complex drivers of life history transitions and reinforcing the need for context-specific policies addressing the vulnerabilities of adolescence worldwide.